2019
DOI: 10.2174/1381612825666190402163940
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany, Phytochemistry and Traditional Uses of Curcuma spp. and Pharmacological Profile of Two Important Species (C. longa and C. zedoaria): A Review

Abstract: Ethnopharmacological relevance: The genus Curcuma, which is the most important source of curcumin, has been widely used in different traditional medicines. Various species of Curcuma have long been used for several purposes such as healing wounds, liver disorders, jaundice and also as a blood purifier. Aim of the study: This review focused on the ethnopharmacological uses and phytochemical aspects of Curcuma. Additionally, in this study, the different properties of two species of Curcuma in Islamic Tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 0 publications
0
66
0
2
Order By: Relevance
“…Turmeric is commonly used as spice, dye, drug and cosmetics [35], but recent research efforts have further characterised its medicinal properties and have identified its biochemical components in high resolution and specificity. The genus Curcuma is rich in flavonoids, tannins, anthocyanin, phenolic compounds, oil, organic acids and inorganic compounds [36]. The biological activities of Curcuma have been attributed to the non-volatile ingredients of the rhizome, cucurminoids (e.g.…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
See 2 more Smart Citations
“…Turmeric is commonly used as spice, dye, drug and cosmetics [35], but recent research efforts have further characterised its medicinal properties and have identified its biochemical components in high resolution and specificity. The genus Curcuma is rich in flavonoids, tannins, anthocyanin, phenolic compounds, oil, organic acids and inorganic compounds [36]. The biological activities of Curcuma have been attributed to the non-volatile ingredients of the rhizome, cucurminoids (e.g.…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
“…curcumin), as well as to the volatile terpenoids [37]. Curcumin has been shown in experiments to have strong anti-inflammatory and antioxidant effects [29,36]. The European Union has recommended the use of numerous medicinal plants for the treatment of gastrointestinal disorders, and among them are ginger root (Z. officinale) and turmeric root (C. longa) [38].…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin, one of the major curcuminoids contained in the rhizome of Curcuma longa (turmeric), is a lipophilic polyphenol that has been used for centuries as an essential tool of traditional medicine in Asia [1]. Nowadays, it is widely used as dietary spice, but also in cosmetic and pharmaceutical industries [2].…”
Section: Introductionmentioning
confidence: 99%
“…Its common name is Narkachur/White turmeric and is found in India and Indonesia. It contains curcumenol, procurcumenol, zederone and comosone II [102,103]. The parts used are the leaves.…”
Section: Curcuma Zedoariamentioning
confidence: 99%